2017
DOI: 10.1016/j.clim.2016.10.007
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of the programmed cell death machinery in innate immune cells to lupus nephritis

Abstract: Systemic lupus erythematosus (SLE) is a chronic multi-factorial autoimmune disease initiated by genetic and environmental factors, which in combination trigger disease onset in susceptible individuals. Damage to the kidney as a consequence of lupus nephritis (LN) is one of the most prevalent and severe outcomes, as LN affects up to 60% of SLE patients and accounts for much of SLE-associated morbidity and mortality. As remarkable strides have been made in unlocking new inflammatory mechanisms associated with si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 204 publications
(265 reference statements)
0
8
0
Order By: Relevance
“…Since the first programmed cell death, apoptosis, described in 1972 by Kerr and his two colleagues [3], other programmed cell death pathways have been defined and intensively investigated, including NETosis, necroptosis, pyroptosis, and autophagy [4, 5]. Indeed, dysregulated cell death in combination with defective clearance of dying cells has been suggested to contribute to the release of damage-associated molecular patterns (DAMPs), amplification of inflammatory and immune responses, production and release of autoantigens, and tissue damage in SLE [68]. In this review, we discuss various forms of programmed cell death pathways with particular emphasis on inflammatory cell death such as NETosis, pyroptosis, and necroptosis and their consequences in the inflammatory and immune responses in SLE.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first programmed cell death, apoptosis, described in 1972 by Kerr and his two colleagues [3], other programmed cell death pathways have been defined and intensively investigated, including NETosis, necroptosis, pyroptosis, and autophagy [4, 5]. Indeed, dysregulated cell death in combination with defective clearance of dying cells has been suggested to contribute to the release of damage-associated molecular patterns (DAMPs), amplification of inflammatory and immune responses, production and release of autoantigens, and tissue damage in SLE [68]. In this review, we discuss various forms of programmed cell death pathways with particular emphasis on inflammatory cell death such as NETosis, pyroptosis, and necroptosis and their consequences in the inflammatory and immune responses in SLE.…”
Section: Introductionmentioning
confidence: 99%
“…SLE is a multifactorial systemic autoimmune disease, characterized by production of abundant autoantibodies [ 3 ]. Increasing evidence has demonstrated that dysregulated cell death and defective removal of dead cells underlie the onset of SLE [ 38 40 ]. In SLE patients, defective removal of dead cells contributes to the exposure of autoantigens and the release of damage-associated molecular patterns (DAMPs), thereby amplifying inflammation and immune responses [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…LN has multiple pathogenic pathways including aberrant apoptosis, autoantibody production and IC deposition with complement activation [1,2]. Apoptotic cell death with roles in tissue damage and immune dysregulation, is involved in the generation of autoantigens and the externalization of modi ed nuclear antigens [3].…”
Section: Discussionmentioning
confidence: 99%
“…Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by a loss of immune tolerance and formation of immune complexes (IC) containing nuclear autoantigens, resulting in in ammation at various organs and tissues, of which damage to the kidney as a consequence of lupus nephritis (LN) is the most common cause of morbidity and mortality [1,2]. Current understanding of the crucial pathogenic mechanisms includes an imbalance between production of apoptotic cells and disposal of apoptotic materials [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation